Anarchy, state, and utopia - Nozick, Robert (Basic Books, a member of the Perseus Books Group, 2013)
"First published in response to John Rawls' A Theory of Justice, Robert Nozick's Anarchy, State, and Utopia has since ingrained itself in contemporary political debates as one of the defining texts in classic libertarian thought. Challenging and ultimately rejecting liberal, socialist, and conservative agendas, Nozick boldly asserts that the rights of individuals are violated as a state's responsibilities increase--and the only way to avoid these violations rests in the creation of a minimalist state limited to protection against force, fraud, theft, and the enforcement of contracts. Translated into 100 languages, winner of the National Book Award, and named one of the 100 most influential books since World War II by the Times Literary Supplement, Anarchy, State, and Utopia remains one of the most theoretically trenchant and philosophically rich defenses of economic liberalism to date. With a new foreword by Thomas Nagel, this revised edition will introduce Nozick and his work to a new generation of readers"--Back cover